2023
DOI: 10.1038/s41467-023-36171-2
|View full text |Cite
|
Sign up to set email alerts
|

Reef islands have continually adjusted to environmental change over the past two millennia

Abstract: Global environmental change is identified as a driver of physical transformation of coral reef islands over the past half-century, and next 100 years, posing major adaptation challenges to island nations. Here we resolve whether these recent documented changes in islands are unprecedented compared with the pre-industrial era. We utilise radiometric dating, geological, and remote sensing techniques to document the dynamics of a Maldivian reef island at millennial to decadal timescales. Results show the magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Further understanding of the geological and geographical variability of reef systems will assist in deciphering how coral reefs will respond to future SLR. Several recent studies based on morphodynamic principles and observations have challenged the assumption that increased flooding due to SLR will automatically render reef islands uninhabitable within decades [110,112]. For instance, results have shown that the magnitude of island change from a range of locations over the past 50 years is not unprecedented compared with paleo-dynamic evidence that has defined large-scale changes in island dimension, shape, and beach levels since island formation c. 1500 years ago.…”
Section: Coral Reefs and Reef Islandsmentioning
confidence: 99%
“…Further understanding of the geological and geographical variability of reef systems will assist in deciphering how coral reefs will respond to future SLR. Several recent studies based on morphodynamic principles and observations have challenged the assumption that increased flooding due to SLR will automatically render reef islands uninhabitable within decades [110,112]. For instance, results have shown that the magnitude of island change from a range of locations over the past 50 years is not unprecedented compared with paleo-dynamic evidence that has defined large-scale changes in island dimension, shape, and beach levels since island formation c. 1500 years ago.…”
Section: Coral Reefs and Reef Islandsmentioning
confidence: 99%
“…Analysis of non-vegetated island shorelines from satellite imagery is typically impossible due to the low contrast between beach sediments and reef flat, and difficulty in accurately identifying the toe of the beach at different tidal stages [27,59]. However, these reef island beaches are just as, if not more, dynamic than the vegetated island cores [29,71,73,81,82]. Excluding non-vegetated areas thus prevents important island evolutionary behaviour from being documented.…”
Section: Implications and Considerationsmentioning
confidence: 99%
“…A number of atoll islet formation models have been previously established from reef sites in the Indo-Pacific domain, assuming that the long-term coral reef islet stability is mainly controlled by sea level changes [19,36,[46][47][48][49]52,55,91,92,[105][106][107][108]. The elevation of the antecedent substrates-e.g., reef flats, conglomerate platforms, lagoonal hard to soft surfaces-close to or at sea level at the time of motu initiation appears to be critical to motu initiation and expansion.…”
Section: Comparaison With Other Coral Reef Isletsmentioning
confidence: 99%